THE INFLUENCE OF CURRENT RATIO, QUICK RATIO AND CASH RATIO, ON RETURN ON ASSETS AT PEMPEK CAWAN PUTIH RESTAURANT PERIOD 2012 – 2021 - Purwanti, Bella; Warasto, Hestu Nugroho (International Journal of Social and Management Studies, 2023)
This study aims to determine simultaneously the influence of the Current Ratio, Quick Ratio, and Cash Ratio variables on Return On Assets at the Pempek Cawan Putih Restaurant for the period 2012 to 2021. The data used in this study is the Financial Report of the Pempek Cawan Putih Restaurant. The research method used is descriptive quantitative in nature. The data analysis technique used is descriptive statistics, simple and multiple analysis using SPSS version 26. The results of this test are that the variable Current Ratio (X1) has a tcount of 0.920 < ttable of 2.44691 and a significance value of 0.384 > 0.05, so it can be concluded that Current Ratio has no effect and is not significant on Return On Assets (Y), Quick Ratio (X2) has a tcount value of 0.537 < ttable of 2.44691 and a significance value of 0.606 > 0.05, it can be concluded that Quick Ratio has no effect and is not significant on Return On Assets (Y), Cash Ratio (X3) has a tcount value of 0.584 <ttable 2.44691 and a significance value of 0.576 > 0.05, it can be concluded that Cash Ratio has no effect and is not significant on Return On Assets (Y), and Current Ratio (X1) ), Quick Ratio (X2), and Cash Ratio (X3) together have fcount > ftable 10.098 > 4.530 and a significance value of 0.009 <0.005, it can be concluded that simultaneously positive and significant impact on Return On Assets (Y).